2019
DOI: 10.1002/nop2.276
|View full text |Cite
|
Sign up to set email alerts
|

Failing to Fail nursing students among mentors: A confirmatory factor analysis of the Failing to Fail scale

Abstract: Aim The aim was to explore the psychometric properties with respect to the internal consistency reliability of the subject‐specific questionnaire “Failing to Fail.” Design Cross‐sectional study. Methods Exploratory factor analysis with varimax rotation. A confirmatory factor analysis was used to examine the factor structure of the “Failing to Fail” scale. The sample included 336 Norwegian nurse mentors. Results The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…In situations where students did not meet performance requirements, some assessors revealed that they found it difficult to fail a student who as a mentor they had befriended. Similar situations are reported in other health professions where assessor and student relationships were found to be an influencing factor in student assessment outcomes [61][62][63] "And if you know them already, like some of the students we work with its hard to make decisions on competency" 3:24:1.…”
Section: Resultsmentioning
confidence: 54%
See 2 more Smart Citations
“…In situations where students did not meet performance requirements, some assessors revealed that they found it difficult to fail a student who as a mentor they had befriended. Similar situations are reported in other health professions where assessor and student relationships were found to be an influencing factor in student assessment outcomes [61][62][63] "And if you know them already, like some of the students we work with its hard to make decisions on competency" 3:24:1.…”
Section: Resultsmentioning
confidence: 54%
“…'Some people get treated differently than others in the assessment, and it's not fair ' 7:246:4 The participants believed assessment should be an objective and fair process, 64,65 and were acutely aware of issues surrounding the adverse impact a fail would have on student progression. 61,64 This was a driver for assessor actions in the process of moderating. Another confounding issue was errors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When developing such a document, it will be important for educational institutions to confer with instructors to identify the document's intended purpose and ensure that it meets those identified needs. Establishing this type of support for teachers would act as an important recognition of the difficulty that teachers often face in making allocation and consequence decisions that can significantly impact a student's academic and personal journey, and would likely reduce occurrence of the "failure to fail" tendency that can lead to unsafe or unprepared practitioners graduating from nursing schools in the future (Bachmann, Groenvik, Hauge, & Julnes, 2019).…”
Section: Implications Of This Study For Educationmentioning
confidence: 99%